The Improving in Competitive Advantage of Education Quality at Private Islamic Junior High Schools in Pringsewu District, Lampung - Supriyadhi, Supriyadhi; Rini, Riswanti; Riswandi, Riswandi; Handoko, Handoko (Abjadia : International Journal of Education, 2023)
This study aims to determine and to examine the influent of visionary leadership and total quality management through organizational culture on the competitive advantage of education quality at Private Islamic Junior High Schools (MTs.) in Pringsewu Regency, Lampung. This research includes quantitative research of the ex-post facto type with a sample of 205 teachers through proportional random sampling. The data collection through documentations and questionnaires, then the results were analyzed by using correlational research methods through regression analysis, path analysis, and Sobel test. The results showed that both directly and indirectly, the variable: visionary leadership, total quality management, and organizational culture partially and simultaneously have the positives and the significant influents on competitive advantage. In percentage terms, competitive advantage is influenced by: visionary leadership is 34.2%, total quality management is 48.8%, organizational culture is 79.8%, and of the three variables are 91.2%, if visionary leadership, total quality management, and organizational culture increase, so that the competitive advantage will also increase.